The importance of logical thinking for clinical nursing care - Francisca Diana da Silva Negreiros; Tatiana Rebouças Moreira; Thereza Maria Magalhães Moreira; Lucilane Maria Sales da Silva; Maria Célia de Freitas; Maria Vilani Cavalcante Guedes (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective To present a reflection on the importance of logical thinking for clinical nursing care. Method Reflection paper Reflection The exercise of an effective clinical care brings with it the need for logical thinking and adequate reasoning for safe and effective nursing practices. Therefore, training based on philosophical principles that encourage the increase of logical and critical thinking is considered unquestionable, ensuring professionals the systematization of assistance with the application of the nursing process based on scientific understanding and strong arguments supported by the path of truthfulness, morality, ethics and critical self-reflection in order to value clinical practices. Final considerations The importance of logical thinking for nursing care is ratified here, supporting nursing care systematization and the nursing process stages. Thus, nurses can use clinical reasoning skills to deliver a humane, ethical, and effective professional performance.